2000
DOI: 10.1111/j.1752-7325.2000.tb03339.x
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health and Nutrition in Older People

Abstract: The theoretical link between foods choice and masticatory efficiency has long been established. Recent evidence has confirmed this association, demonstrating a progressive alteration in food choice with decreasing numbers of teeth, with the greatest effect being among those who are edentulous. This altered food selection results in significant differences in the hematological status for some key nutrients in the one study in which this association was investigated. This paper summarizes some of the literature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
130
0
8

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(139 citation statements)
references
References 41 publications
1
130
0
8
Order By: Relevance
“…Além disso, a diminuição do consumo de fibras, frutas e vegetais, decorrente da capacidade mastigatória alterada está associada com aumento do risco cardiovascular. Sabe-se também que frutas e vegetais diminuem o risco de câncer gástrico, esofágico e coloretal 25 . Corroborando esta informação, estudo americano em Iowa 26 , em uma amostra de 220 residências, evidenciou que a média de consumo de nutrientes foi significativamente menor nos sujeitos que tiveram menos dentes naturais ou funcionais ou problemas de oclusão das próteses.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Além disso, a diminuição do consumo de fibras, frutas e vegetais, decorrente da capacidade mastigatória alterada está associada com aumento do risco cardiovascular. Sabe-se também que frutas e vegetais diminuem o risco de câncer gástrico, esofágico e coloretal 25 . Corroborando esta informação, estudo americano em Iowa 26 , em uma amostra de 220 residências, evidenciou que a média de consumo de nutrientes foi significativamente menor nos sujeitos que tiveram menos dentes naturais ou funcionais ou problemas de oclusão das próteses.…”
Section: Discussionunclassified
“…Tal deficiência alimentar pode levar à perda de peso corpóreo e à desnutrição 8 . Todavia, sabe-se que a manutenção de um estado nutricional adequado não significa, necessariamente, maior sobrevida, mas interfere positivamente para que as pessoas aproximemse do seu ciclo máximo de vida 25 . Estudo de uma coorte chinesa, com 29.584 adultos saudáveis, mostrou que perda dentária foi significativamente associada com morte geral, morte por câncer gastrointestinal, doença cardíaca e AVC 27 .…”
Section: Discussionunclassified
“…5 The negative impact of poor oral conditions on daily life is particularly significant among edentulous patients. 6,7 Edentulism is prevalent among older people, especially dependent elderly and is highly associated with socioeconomic status. 8 Removable dentures especially complete denture are frequent among older people.…”
Section: Introductionmentioning
confidence: 99%
“…Walls et al [2] stated that dentition is a significant factor for efficient chewing, which is important for the maintenance of bodily nutrition as well as systemic, psychological, and physical functions. However, other studies have suggested that nutrition does not improve after the fitting of new dentures [3][4][5].…”
Section: Introductionmentioning
confidence: 99%